Which agreements boost agricultural trade in Africa? - Aboushady, Nora; Ramzy, Myriam; Zaki, Chahir (AKADEMIYA2063, 2023)
One of the main features of today’s global trade system is the proliferation of regional trade agreements (RTAs). Over the past four decades, the number of agreements increased from just 15 in 1980 to 583 in 2023 (WTO 2023). Most of the 583 agreements are free trade agreements (FTAs) (317), followed by economic integration agreements (190), partial scope agreements (27), and customs unions (18). The proliferation of RTAs in recent years has been coupled with broader and deeper coverage under these agreements. Broader coverage increasingly includes more policy areas that may be trade-related (tariffs and nontariff measures) or non trade-related (behind-the-border policies, intellectual property rights, movement of capital and people, competition policy, and others). In this regard, the scope of RTAs has been expanded by WTO members and signatories of RTAs from just 8 policy areas in the 1950s to 17 policy areas today. Deeper agreements include an increasing number of commitments within each policy area (Fernandes et al. 2021). They are also increasingly accompanied by legal requirements, such as stronger transparency and enforcement mechanisms (Abman et al. 2021, Fernandes et al. 2021). Thus, RTAs are increasingly being converted to deep trade agreements.